El marxismo y la liberación de las mujeres trabajadoras: de la Internacional de Mujeres Socialistas a la Revolución Rusa - Gaido, Daniel (Ariadna Ediciones, 2016)
History of women's organization within the international socialist movement of the late nineteenth and early twentieth century.